2023
DOI: 10.2147/copd.s385186
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Evidence on the Diagnostic and Clinical Characteristics of Asthma in Japanese Patients with COPD: The ACO Japan Cohort Study

Abstract: Introduction The ACO Japan Cohort Study, a multicenter observational study, investigated the proportion of patients with chronic obstructive pulmonary disease (COPD) who met the Japanese Respiratory Society (JRS) asthma–COPD overlap (ACO) diagnostic criteria, characteristics of ACO and non-ACO patients, and the patient transitions between ACO/non-ACO diagnosis over 2 years. Patients and Methods Patients with COPD were consecutively enrolled between June and December 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…21 A 2-year multicenter cohort study of Japanese patients with COPD reported that patients with COPD who had ACO as per the JRS criteria were at a higher risk of exacerbations and rapid decline in respiratory function than those without ACO; moreover, it demonstrated that the JRS criteria for ACO were useful in identifying high-risk patients with COPD. 22 This study was based on patients with an asthma diagnosis based on one year of receipts among patients diagnosed with COPD. It is possible that non-respiratory specialists did not perform respiratory function tests and established an asthma diagnosis based on symptoms alone, which may have led to an overestimation of the incidence of complications.…”
Section: Discussionmentioning
confidence: 99%
“…21 A 2-year multicenter cohort study of Japanese patients with COPD reported that patients with COPD who had ACO as per the JRS criteria were at a higher risk of exacerbations and rapid decline in respiratory function than those without ACO; moreover, it demonstrated that the JRS criteria for ACO were useful in identifying high-risk patients with COPD. 22 This study was based on patients with an asthma diagnosis based on one year of receipts among patients diagnosed with COPD. It is possible that non-respiratory specialists did not perform respiratory function tests and established an asthma diagnosis based on symptoms alone, which may have led to an overestimation of the incidence of complications.…”
Section: Discussionmentioning
confidence: 99%